Susceptibility of Candida albicans, Staphylococcus aureus, and Streptococcus mutans biofilms to photodynamic inactivation: an in vitro study - Pereira, Cristiane Aparecida [UNESP]; Romeiro, Rogerio Lima [UNESP]; Borges Pereira Costa, Anna Carolina [UNESP]; Silva Machado, Ana Karina [UNESP]; Junqueira, Juliana Campos [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP] (Springer London Ltd, 2011)
The purpose of this study was to evaluate specific effects of photodynamic inactivation (PDI) using methylene blue as photosensitizer and low-power laser irradiation on the viability of single-, dual-, and three-species biofilms formed by C. albicans, S. aureus, and S. mutans. Biofilms were grown in acrylic discs immersed in sterile brain heart infusion broth (BHI) containing 5% sucrose, inoculated with microbial suspension (10(6) cells/ml) and incubated for 5 days. on the fifth day, the effects of the methylene blue (MB) photosensitizer at a concentration of 0.1 mg/ml for 5 min and InGaAlP laser (660 nm) for 98 s, alone and conjugated were evaluated. Next, the discs were placed in tubes with sterile physiological solution [0.9% sodium chloride (NaCl)] and sonicated for to disperse the biofilms. Ten-fold serial dilutions were carried and aliquots seeded in selective agar, which were then incubated for 48 h. Then the numbers CFU/ml (log(10)) were counted and analyzed statistically (ANOVA, Tukey test, p < 0.05). Scanning electron microscopy (SEM) on discs treated with PDI and control biofilms groups was performed. Significant decreases in the viability of all microorganisms were observed for biofilms exposed to PDI mediated by MB dye. Reductions (log(10)) of single-species biofilms were greater (2.32-3.29) than the association of biofilms (1.00-2.44). Scanning electron microscopy micrographs suggested that lethal photosensitization occurred predominantly in the outermost layers of the biofilms. The results showed that PDI mediated by MB dye, might be a useful approach for the control of oral biofilms.
Keywords: Biofilm; Candida albicans; Staphylococcus aureus; Streptococcus mutans; Photodynamic inactivation